Plasma galectins and metabolites in advanced head and neck carcinomas: evidence of distinct immune characteristics linked to hypopharyngeal tumors - Bao-Tram Thi Tran; Aurore Gelin; Sylvère Durand; Matthieu Texier; Amaury Daste; Clémence Toullec; Karim Benihoud; Ingrid Breuskin; Philippe Gorphe; Florence Garic; Catherine Brenner; Christophe Le Tourneau; et al. (OncoImmunology)
Extra-cellular galectins 1, 3 and 9 (gal-1, −3 and −9) are known to act as soluble immunosuppressive agents in various malignancies. Previous publications have suggested that their expression is dependent on the metabolic status of producing cells and reciprocally that they can influence metabolic pathways in their target cells. Very little is known about the status of gal-1, −3 and −9 in patients bearing head and neck squamous cell carcinomas (HNSCC) and about their relationships with the systemic metabolic condition. This study was conducted in plasma samples from a prospective cohort of 83 HNSCC patients with advanced disease. These samples were used to explore the distribution of gal-1, −3 and −9 and simultaneously to profile a series of 87 metabolites assessed by mass spectrometry. We identified galectin and metabolic patterns within five disease categories defined according to the primary site and human papillomavirus (HPV) status (HPV-positive and -negative oropharyngeal carcinomas, carcinomas of the oral cavity, hypopharynx and larynx carcinomas). Remarkably, samples related to hypopharyngeal carcinomas displayed the highest average concentration of gal-9 (p = .017) and a trend toward higher concentrations of kynurenine, a potential factor of tumor growth and immune suppression. In contrast, there was a tendency toward higher concentrations of fatty acids in samples related to oral cavity. These observations emphasize the diversity of HPV-negative HNSCCs. Depending on their primary site, they evolve into distinct types of immune and metabolic landscapes that seem to be congruent with specific oncogenic mechanisms.